PERSEPSI SISWA TENTANG KETERAMPILAN VARIASI GURU MENGAJAR, LINGKUNGAN KELUARGA DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR PADA MATA PELAJARAN EKONOMI SISWA KELAS XI IPS SMA NEGERI KOTA BATAM - Sri Arita; Susi Evanita (Program Magister Pendidikan Ekonomi (S2), 2014)
The purpose of this study was to analyze the effect : 1) Student perceptions about teacher variation skill of teaching to learning motivation, 2) the family environment to the learning motivation, 3) Student perception about teacher variation skill of teaching to the learning outcomes, 4) the family environment to the learning outcomes, 5)Student perception about teacher variation skill of teaching, family environment and learning motivation to learning outcomes. Techniques of data analysis is descriptive analysis, test analysis and hypothesis testing requirements with path analysis. The results of this study found that : 1) Student perceptions about teacher variation skill of teaching have positive impact and significant to learning motivation, 2) the family environment influence have positive impact and significant to the learning motivation, 3) Student perception about teacher variation skill of teaching influenced have positive impact and significant the learning outcomes , 4) the family environment influence significantly have positive impact and significant to the learning outcomes, 5) Student perception about teacher variation skill of teaching, family environment and learning motivation to learning outcomes.